Novel Method for Laparoscopic Common Bile Duct Exploration Performed Using a Disposable Bronchoscope (Ambu® aScope TM) - Aawsaj, Yousif Mahmood; Ibrahim, Ibrahim K; Gilliam, Andrew (Kurdistan Journal of Applied Research, 2017)
Laparoscopic common bile duct (CBD) exploration can be performed following choledocotomy or via the trancystic approach. Laparoscopic CBD exploration is limited in some benign upper gastrointestinal units due to the cost of sterilization of the re-usable choledochoscope. We have recently published a case series confirming the safety and efficacy of the 5mm re-usable bronchoscope for CBD exploration. This case series evaluates a single-use bronchochoscope (Ambu aScopeTM) for laparoscopic CBD exploration. Data were collected from electronic records of the patients from January 2015 until December 2016; all the cases had confirmation of CBD stones. Twenty-one patients had CBD exploration using the disposable bronchochoscope. There were 7 male and 14 female (median age 42). 8 procedures were performed as emergencies and 13 were performed electively. All the cases were done laparoscopically apart from one planned as an open procedure due to previous extensive open surgery. Twenty cases had their CBD cleared using disposable bronchoscope and one needed subsequent special test follow up. Choledocotomy was performed in 15 and Tran’s cystic approach was performed in 6. No T-tube was used in the laparoscopic cases. 2 cases were performed as day case surgery. Median postoperative hospital stay was 2.5 days. In conclusion, the disposable bronchoscope is safe and effective for use in CBD exploration with results comparable to our previously published case series. It has guaranteed sterility and is cost effective compared to the re-usable bronchoscope especially when initial capital outlay, sterile processing and maintenance costs are considered.